Applicability of potentially probiotic Lactobacillus casei in low-fat Italian type salami with added fructooligosaccharides: in vitro screening and technological evaluation. (October 2020) - Bis-Souza, Camila Vespúcio; Penna, Ana Lucia Barretto; da Silva Barretto, Andrea Carla
Abstract: The aim was to evaluate the use of Lactobacillus casei strains in the fermentation process of low-fat Italian type salami with fructooligosaccharides (FOS). A screening using probiotic strains was performed at pH 5.5, 5.0 and 4.5 and incubation temperatures of 15 and 25 °C. Lactobacillus casei SJRP66 and Lactobacillus casei SJRP169 were selected and added to the low-fat fermented sausage – C (control), FOS (25% reduced fat with 2% FOS), FOS_66 (25% reduced fat with 2% FOS and L.casei SJRP 66) and FOS_169 (25% reduced fat with 2% FOS and L.casei SJRP 169). The evaluation included pH, moisture, lactic acid bacteria count, probiotic count, weight loss, instrumental color, TBARS and texture parameters. FOS_66 and FOS_169 presented a good probiotic count (8 log CFU/g) and similar technological behavior to the control. The addition of the probiotic showed no effect on lipid oxidation and * value. These strains of probiotic showed promising properties for applications in low-fat Italian type salami with healthier appeal. Highlights: Potentially probiotic strains were used to in vitro trail with adverse conditions. SJRP 66 and SJRP 169 show highest viability in the in vitro test. The low-fat salami with FOS and Lactobacillus casei presented high cell count. The technological performance during ripening was not affected by the probiotic. Those strategies proved to be useful to obtains a healthier meat product.